2011
DOI: 10.1063/1.3586270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heart rate variability signal in meditation using second-order difference plot

Abstract: In this article, the heart rate variability signal taken from subjects practising different types of meditations have been investigated to find the underlying similarity among them and how they differ from the non-meditative condition. Four different groups of subjects having different meditation techniques are involved. The data have been obtained from the Physionet and also collected with our own ECG machine. For data analysis, the second order difference plot is applied. Each of the plots obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Most of the meditation techniques work by affecting the Autonomic Nervous system (ANS), in turn regulating many organs and muscles, controlling functions such as the heartbeat, sweating, breathing, and digestion. Heart rate variability (HRV) is a popular noninvasive tool to assess different heart conditions and now it has been observed that it reflects some psychological conditions also [5]. The analysis of heart rate variability (HRV), the variation of period between consecutive heart beats, provides valuable information to assess the ANS.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the meditation techniques work by affecting the Autonomic Nervous system (ANS), in turn regulating many organs and muscles, controlling functions such as the heartbeat, sweating, breathing, and digestion. Heart rate variability (HRV) is a popular noninvasive tool to assess different heart conditions and now it has been observed that it reflects some psychological conditions also [5]. The analysis of heart rate variability (HRV), the variation of period between consecutive heart beats, provides valuable information to assess the ANS.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the major axis was found to increase in the meditation state compared to premeditation state and hence the two states to have different physiology. 20 Goswami et al 21 used second-order difference plot to visually differentiate meditative state from normal physiological state. They found that in the state of meditation the rates of HRVs correlate with each other and the external stimuli do not affect the physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As an implication they concluded that the meditative states have a completely different physiology from the non-meditative states. 21 Poincaré plot analysis and sequence trend analysis. An important advantage of both of these methods is that they are independent of the stationarity of the RR interval time series.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, functions of heartbeat, sweating, breathing, and digestion are controlled by the ANS. Recent studies highlighted the psycho-physiological aspects of meditation and its effect [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Abstract -2d and 3d Poincaré Plot 3d Frequency Delay Plot mentioning
confidence: 99%
“…Accordingly, functions of heartbeat, sweating, breathing, and digestion are controlled by the ANS. Recent studies highlighted the psycho-physiological aspects of meditation and its effect [5][6][7][8][9][10][11][12][13][14][15].Typically, the HRV is a popular non-invasive tool to assess different conditions of heart [16][17][18][19]. Nowadays, it is observed that HRV reflects some psychological conditions [20,21].…”
mentioning
confidence: 99%